Analisis Peran Content marketing, Live streaming, Product quality dalam Meningkatkan Customer satisfaction dan Repurchase intention Konsumen Produk Thrift - Chikita Putri Prameswari; Usep Suhud; Meta Bara Berutu (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study investigates the impact of content marketing, live streaming, and product quality on customer satisfaction and repurchase intention among thrift product consumers on TikTok. Utilizing a quantitative method, data were collected through an online survey of 270 respondents aged 17 and above residing in Jakarta, all of whom had purchased thrift products on TikTok at least once within the past six months. The analysis was conducted using Structural Equation Modeling (SEM) with SPSS 26 and AMOS 29. The findings reveal that all proposed variables significantly and positively influence customer satisfaction and repurchase intention. While content marketing and live streaming effectively attract consumer attention, their impact on repurchase intention depends largely on the clarity and reliability of the information delivered. Product quality emerged as the most influential factor affecting both satisfaction and loyalty. Furthermore, customer satisfaction was found to have a direct and significant effect on repurchase intention, highlighting its crucial role in fostering consumer loyalty in social commerce. This study emphasizes the importance of transparent content, interactive live sessions, and consistent product quality in building long-term customer relationships in the digital thrift market.